Economic Reforms and the Rate of Returns to Schooling in China’s Transition - Dong, Han Bing (Université d'Ottawa | University of Ottawa, 2007)
This paper replicates Li (2003's work on the rates of returns to education in urban China based on the data from the second cycle of the Chinese Household Income Project (CHIP-95). This data set is released by "The Inter-university Consortium for Politica